Incidence of Pneumonia on the Nutritional Status of Young Children in the Work Room of the Antang Public Health Center, Makassar South Sulawesi - Nursiah, Andi; Pannyiwi, Rahmat; Syamsinar, A.; Muchsin, Wachyudi; Masdarwati, Masdarwati; Ali, St. Aminah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Pneumonia is infection network lungs Which nature I reason his is bacteria, virus, mold, exposure material chemistry or damage physique from bacterial lungs Which normal cause pneumonia is Streptococcus and Mycoplasma Pneumonia, whereas virus which cause pneumonia is Adenoviruses, Rhinovirus, Influenza Virus, Respiratory Syncytial Virus. The aim of this study to find out the relationship between nutritional status and the incidence of pneumonia in toddlers In Region Work Public health center Antang. Type study This is method study analytical observation with a cross sectional approach. This research was carried out in part Antang health center working area. population in study this all toddler which visit in Public health center Antang. Technique taking sample use simple random sampling. The data analysis carried out was univariate analysis and bivaruate analysis. Test that on used is the chi square statistical test with another alternative test, namely the Fisher Excat test with level meaning p=0 .02 so HA accepted Because proven to exist connection knowledge Mother pregnant with attitude with p<0.05. Concluded there is connection Between Nutritional Status and the Incidence of Pneumonia in Toddlers in Community Health Center Working Areas Antang. Based on results study this, as good as his officer health especially midwife collaborate with health agencies that hold outreach and outreach activities so that they can increase knowledge, and information person related old pneumonia treatment on toddler.